Synthesis of new heterocyclic compounds based on 1,4-naphthoquinones and azomethines of α-amino acids - Kudrinetska, Anastasiia; Shakh, Yurii; Bolibrukh, Khrystyna; Karkhut, Andrii; Lytvyn, Bohdan; Polovkovych, Sviatoslav (Видавництво Львівської політехніки, 2013)
Analysed the literature sources to establish the basic ˝skafolds ˝, necessary for the design of "drugs-like molecules." Created the combinatorial library of new heterocyclic derivatives of 1,4-naphthoquinone. A docking study for determining structure leaders was conducted, ways of optimization the chemical structures to enhance the biological activity were determined. Designed by methods of obtaining a new heterocyclic derivatives based on 1,4-naphthoquinone and conducted search including effective anti-cancer agents.
Keywords: heterocyclic compounds; 1,4-naphthoquinones; azomethines of α-amino acids; anticancer agents; "drug-like" compounds; 1,3-dypolar cycloaddition reaction